Što i kamo s Meštrovićem? - Vuković, Mladen, književnik (Array, 2008)
The most prolific science writer of Croatian origin in the US academic community is sociologist Stjepan Gabrijel Meštrović (born in Zagreb in 1955), who has lectured in sociology at the American university of Texas A&M for almost two decades, written fifteen books and published over fifty research papers in eminent international journals – so it was with particular attention that the readership awaited his book Srce od kamena – Moj djed Ivan Meštrović (Heart of Stone – My Grandfather Ivan Meštrović). This sociological book has shed an entirely new light on the life and work of the famed sculptor, in spite of the impression that everything had been said about Ivan, as international databases record about six thousand bibliographic entries concerning Meštrović.